Ежик и его друзья: [сказки] / Надежда Притулина ; художник Анна Зобнинская - Притулина Надежда Петровна (Алтей-Бук, 2018)
Экземпляры: (20200117) / Инвентарный номер: 50482 / Цена: 100.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: П 77 / ББК: 84(2=411.2)6